Evaluasi Penerapan Realistic Mathematics Education Berbantuan GeoGebra Terhadap Pemahaman Konsep Matematis Menggunakan Model CIPP - Ramadhan, Farizal; Mahmudi, Ali; Rahman, M. Tata Aulia (Mandalika Mathematics and Educations Journal, 2025)
The purpose of this study is to evaluate the effectiveness of using the Realistic Mathematics Education (RME) approach assisted by GeoGebra in teaching mathematics at a public junior high school in the city center. To assess the extent to which the implementation of RME meets the desired learning standards, the CIPP model (Context, Input, Process, Product) was applied. Data were collected through interviews, observations, and document analysis, and analyzed using a descriptive-evaluative method. The findings reveal that the implementation of RME assisted by GeoGebra generally meets the required criteria. The context component reached 100%, input 80%, while the process and product components achieved 85% and 100%, respectively, all of which are categorized as highly appropriate. Nevertheless, several challenges were identified, including limited internet access for using GeoGebra, the lack of professional certification among some teachers, and less-than-ideal instructional time. Overall, the RME approach assisted by GeoGebra proved effective in enhancing students’ conceptual understanding of mathematics, particularly on the topic of three-dimensional shapes such as cubes and rectangular prisms. The average score of students’ conceptual understanding increased significantly from 47.76% in the pretest to 80.29% in the posttest, with the indicator “restating a concept” showing the highest improvement at 93.27%.